Ḥayāt-i Sult̤ānī : yaʻnī savāniḥ ʻumrī Firdaus-i āshiyāṉ ʻAlyā Ḥaz̤rat Navāb Sut̤ān Jahāṉ Begam, Taj-i Hind, farmāṉ ravāʼe Bhūpāl - Zubairī, Muḥammad Amīn (SAMP early 20th-century Indian books project, 1939)
On the life of Sultan Jahan Begam, 1858-1930, Nawab of Bhopal.